Natural Killer Cells in the Malignant Niche of Multiple Myeloma - Venglar, Ondrej; Bago, Julio Rodriguez; Motais, Benjamin; Hajek, Roman; Jelinek, Tomas (Frontiers in Immunology, 2022)
Natural killer (NK) cells represent a subset of CD3- CD7+ CD56+/dim lymphocytes with cytotoxic and suppressor activity against virus-infected cells and cancer cells. The overall potential of NK cells has brought them to the spotlight of targeted immunotherapy in solid and hematological malignancies, including multiple myeloma (MM). Nonetheless, NK cells are subjected to a variety of cancer defense mechanisms, leading to impaired maturation, chemotaxis, target recognition, and killing. This review aims to summarize the available and most current knowledge about cancer-related impairment of NK cell function occurring in MM.